Comparative study of Retrograde Intrarenal Surgery and Mini-Percutaneous Nephrolithotomy among Renal Stone Patients: Mini-PCNL Versus RIRS in Renal Stones - Maqsood Zahid, Muhammad; Farook, Khalid; Ahmad, Khaleel; Ali, Liaquat; Muhammad Javed, Hafiz; Mehmood Ul Hassan, Syed (Pakistan Journal of Health Sciences, 2023)
Mini-Percutaneous Nephrolithotomy (Mini-PCNL) and Retrograde intra-renal surgery (RIRS), can be carried out in a single stage or numerous phases depending on the burden, size, and/or location of the stone. Objective: To check the efficacy of Mini-Percutaneous Nephrolithotomy and Retrograde intra-renal surgery on adult patients with a renal stones. Methods: A total of 101 patients were included who underwent RIRS (n=51) or mini-PCNL (n=50) at Doctors Hospital Jail Chowk in Gujrat, Pakistan in 2021. Retrospective observations were made on 101 individuals who received RIRS or mini-PCNL. Results: The mean hospital stay time was significantly lower in RIRS group i.e., 01.81 ± 0.59 days as compared to mini-PCNL group (p value <0.001). The operation time was 63.72 ± 14.94 minutes for mini-PCNL and 72.65 ± 15.83 minutes for RIRS group. The stone clearance rate was 92% in mini-PCNL group and 82.35% in RIRS group. Conclusions: In conclusion, we found that both mini-PCNL and RIRS are safe and effective ways to treat renal calculi. RIRS is a non-invasive, practical therapeutic option with reduced hospitalizations times, morbidity, and complication rates for these individuals.